Thermally-induced phase transformation sequence of arc evaporated Ta–Al–N coatings. (1st March 2016) - Koller, C.M.; Kirnbauer, A.; Rachbauer, R.; Kolozsvári, S.; Mayrhofer, P.H.
Abstract: Differential scanning calorimetry and thermogravimetric analyses combined with XRD and TEM investigations demonstrate that single-phase face-centred cubic Ta0.89 Al0.11 N1.2 coatings decompose into wurtzite AlN and hexagonal Ta2 N phases upon vacuum annealing to 1500 °C. The Ta2 N phase transformation proceeds via hexagonal Ta5 N6 at 1000 °C and hexagonal ε-TaN at 1100 °C. A significant N2 -loss between 1300 °C and 1500 °C, without a structural change of the Ta2 N phase, suggests the formation of TaN0.3 —at the Ta-rich Ta2 N phase field. Graphical abstract: